Urethral Stricture; Etiology, Presentation, Complications, and Outcome of Management at Gezira State, Central Sudan - Mansour, Mustafa Omran; Aboagla, Yassir Abdalla Bakheet; Taha, Sami Mahjoub; Khalid, Khalid Eltahir (Gezira Journal of Health Sciences, 2013)
Objectives: The objective is to evaluate urethral strictures in term of etiological factors, presentations and management at GHRDS, Gezira State, Central Sudan. Patients and Methods: One hundred sixty patients, who were diagnosed as urethral stricture, were enrolled in this study. All patients were dealt with through a scientific stratum of a thorough work up and managed according to the EAU guidelines. The bio-data, etiological factors of strictures, presenting symptoms and signs, the pathological types and modalities of treatment were recorded and analyzed. Results: The total number of patients was 160 , only two females and the rest were males. The mean age was 46.2 ±2 years. The etiological factors were: post-surgical in 67 patients (41.9%), gonococcal urethritis in 48 patients (30%) followed by post traumatic stricture in 28 patients (17.5%). Concerning the sites 41 (25.6%) patients had bulbar urethral stricture and 24 (15%) with membranous urethra strictures. One hundred forty two (88.8%) patients were treated with visual internal urethrotomy (VIU) and the outcome of treatment was comparable to the literature Conclusion: The commonest etiological factors for urethral strictures in GHRDS were post-surgery followed by gonococcal urethritis. The outcome of management was comparable.